Analysis of Service Quality Dimensions: Towards a Student Satisfaction Model in the “New Normal” - Ladybird Y. Quiachon; Maybelle Paulino (East Asian Journal of Multidisciplinary Research, 2023)
The recent pandemic compelled universities and colleges worldwide to provide services different from usual. This change and the increasing competitive intensities demand higher performance levels globally in Higher Education Institutions (HEIs). To achieve the desired performance levels, universities and colleges must identify well-performing areas and areas needing improvement. One way to identify these areas is by surveying students’ satisfaction. Many studies have been conducted on student satisfaction in public and private universities worldwide. However, students’ satisfaction with the “new normal” has not been fully explored. This study conceptualizes student satisfaction by developing a framework that integrates the service quality dimensions in the “new normal.” Results, conclusions, and recommendations are discussed.